Gingival Hyperplasia as an Early Diagnostic Oral Manifestation in Acute Monocytic Leukemia: A Case Report - Demirer, Serhat; Özdemir, Hakan; Şencanc, Mehmet; Marakoğlud, Ismail (European Journal of Dentistry, 2007)
Acute Myeloblastic Leukemia (AML) is a malignant disease of bone marrow. Due to its high morbidity rate, early diagnosis and appropriate medical therapy is essential. Rapidly forming gingival hyperplasia is usually the first sign of this disease. This case report describes a 17-year-old female who presented rapid gingival overgrowth together with gingival bleeding in only two weeks time. A medical consultation was asked from hematology clinics and after a detailed medical examination Acute Monocytic Leukemia (FAB M5) was rendered. Chemotherapy was the choice of treatment. The patient responded well to chemotherapeutic induction regimen and after two months of medical therapy disease remised and gingival hyperplasia regressed. This case report shows that the gingival hyperplasia may represent an initial manifestation of an underlying systemic disease. Also, early medical therapy in acute monocytic leukemia may resolve the gingival hyperplasia that companies the disease progression. (Eur J Dent 2007;2:111-114)
Keywords: Acute monocytic leukemia; Gingival hyperplasia